Did the Prison Industrial Complex Deliver on Its Promise?: Prison Proliferation and Employment in Rural America - Zhang, Yiwen (The British journal of criminology, 2024)
Two concurrent phenomena emerged in rural America in the 1970s: job losses due to deindustrialization and prison proliferation relating to mass incarceration. While supporters of the prison industrial complex promised an economic lifeline for rural America, opponents questioned the economic benefits of prison openings. Using county fixed-effects models and data covering 1960-2000, this study reveals a null association between prison openings and total rural employment. While prison proliferation marginally increased government employment, it simultaneously had a negative impact on private employment. Specifically, prison openings were associated with decreased employment in manufacturing, finance and recreational services; and had no impact on jobs in construction, wholesale, and local retail sales. Thus, the promises of employment growth relating to prisons were, overall, not kept.